THE INFLUENCE OF ELECTROMAGNETIC EHF WAVES ON THE BACKGROUND IMPULSE ACTIVITY OF SUPRAOPTIC NUCLEUS NEURONS OF HYPOTHALAMUS OF RATS (Proceedings of the YSU B: Chemical and Biological Sciences, 2005)
In conditions of acute experiment on rats anaesthetized by nembutal (40 mg/kg, interperitoniaily) the registration and analysis of background impulse activity of supraoptic nucleus' neurons of rats’ hypothalamus in norm and after electromagnetic irradiation of extremely high frequency on organism were carried out. Changes of neurons background impulse activity mainly related to internal structure of recorded impulse flows were revealed. It was shown that significant shifts generally are observed in the character of dynamics of neuronal current flows. Statistically significant changes of average frequency of neuronal impulsation were not observed.
Keywords: rats; supraoptic nucleus' neurons; hypothalamus; background impulse activity; electromagnetic irradiation of extremely high frequency